2000
DOI: 10.1108/09596110010309934
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of multicultural training practices in the restaurant industry: the training cycle approach

Abstract: The restaurant industry is dealing with diversity in terms of its workforce, international customers and multinational business operations. Acknowledging diversity through multicultural training is beginning to appear in some restaurant companies. This study investigates how franchised restaurants utilize multicultural training programs from a training cycle approach. The findings indicate that high employee turnover rates are the primary reason that the majority of companies do not have a cultural diversity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 13 publications
0
31
0
Order By: Relevance
“…That is, there is potential bias in published literature because it tends to focus on studies with high response rate or significant relationships (De Long and Lang, 1992). Lucas (1999) identified that the most important factor contributing to the generally lower response rate to surveys in the hospitality industry is the fragmented Atkinson and Brown (2001) Performance measure Various size hotels 20% (23) Johnson (1999) Management contract Large hotels 20% (50) Lee and Chon (2000) Training practices Various size restaurants 20% (61) Formica and McCleary (2000) Management skills Large hotels 24% (98) Brown and Dev (1999) Performance measure Large hotels 25% (420) Jenkins (2001) Finance Large hotels 26% (35) Perdue et al (2000) Management skills Leisure clubs 29% (128) Buultjens and Howard (2001) Employment relations Registered clubs 32% (435) Gray et al (2000) Marketing Hospitality industry 33% (329) Beck and La Lopa (2001) Career paths Large hotels 36% (447) Feng and Pearson (1999) Selection criteria and skills Large hotels 42% (133) Wilson et al (2000) Skills-contract catering Catering establishments 42% (56) Ghiselli and Ismail (1999) Organisation behaviour Food services industry 43% (196) Mutch (2001) Career paths Pubs of all sizes 43% (99) Harris and Mongiello (2001) Key performance indicators Large hotels 44% (175) Davidson et al (2001) Organisational behaviour Large hotels 44% (616) Lubetkin (1999) Marketing Bed and breakfast 47% (92) Harris and Bonn (2000) Training Foodservice industry 50% (149) Crotts et al (2001) Organisational behaviour Restaurants 53% (79) Li and Leung (2001) Profile and career of female managers Medium/Large hotel 55% (82) Nield and Kozak (1999) Quality Certification Large hospitality enterprises 69% (34) Karamustafa (2000) Marketing Various size hotels (convenient sampling)…”
Section: Potential Response Ratesmentioning
confidence: 98%
“…That is, there is potential bias in published literature because it tends to focus on studies with high response rate or significant relationships (De Long and Lang, 1992). Lucas (1999) identified that the most important factor contributing to the generally lower response rate to surveys in the hospitality industry is the fragmented Atkinson and Brown (2001) Performance measure Various size hotels 20% (23) Johnson (1999) Management contract Large hotels 20% (50) Lee and Chon (2000) Training practices Various size restaurants 20% (61) Formica and McCleary (2000) Management skills Large hotels 24% (98) Brown and Dev (1999) Performance measure Large hotels 25% (420) Jenkins (2001) Finance Large hotels 26% (35) Perdue et al (2000) Management skills Leisure clubs 29% (128) Buultjens and Howard (2001) Employment relations Registered clubs 32% (435) Gray et al (2000) Marketing Hospitality industry 33% (329) Beck and La Lopa (2001) Career paths Large hotels 36% (447) Feng and Pearson (1999) Selection criteria and skills Large hotels 42% (133) Wilson et al (2000) Skills-contract catering Catering establishments 42% (56) Ghiselli and Ismail (1999) Organisation behaviour Food services industry 43% (196) Mutch (2001) Career paths Pubs of all sizes 43% (99) Harris and Mongiello (2001) Key performance indicators Large hotels 44% (175) Davidson et al (2001) Organisational behaviour Large hotels 44% (616) Lubetkin (1999) Marketing Bed and breakfast 47% (92) Harris and Bonn (2000) Training Foodservice industry 50% (149) Crotts et al (2001) Organisational behaviour Restaurants 53% (79) Li and Leung (2001) Profile and career of female managers Medium/Large hotel 55% (82) Nield and Kozak (1999) Quality Certification Large hospitality enterprises 69% (34) Karamustafa (2000) Marketing Various size hotels (convenient sampling)…”
Section: Potential Response Ratesmentioning
confidence: 98%
“…While hospitality workforces are traditionally multicultural (Iverson, 2000;Lee and Chon, 2000), with only a few exceptions the cruise industry recruits virtually all of its employees from countries other than the United States, bringing together a mix of nationalities to serve predominantly American passengers. It is not unusual to have employees from over forty different countries on one of the larger ships.…”
Section: Nature Of Staff: the Composition And Characteristics Of The mentioning
confidence: 99%
“…Hence, employing bilingual middle managerial staff, translating organizational materials into various languages, and using visual aids such as posters and pictures can facilitate internal communication and can improve EWA (Madera et al, 2013). Hotels shall provide diversity training programs in which interpersonal cross-cultural skills can be developed (Lee and Chon, 2000).…”
Section: Managerial Implicationsmentioning
confidence: 99%